Interferon-γ augments GABA release in the developing neocortex via nitric oxide synthase/soluble guanylate cyclase and constrains network activity - Döhne, Noah; Falck, Alice; Janach, Gabriel M. S.; Byvaltcev, Egor; Strauss, Ulf (Frontiers in Cellular Neuroscience, 2022)
Interferon- γ (IFN-γ), a cytokine with neuromodulatory properties, has been shown to enhance inhibitory transmission. Because early inhibitory neurotransmission sculpts functional neuronal circuits, its developmental alteration may have grave consequences. Here, we investigated acute effects of IFN-γ on -amino-butyric acid (GABA)ergic currents in layer 5 pyramidal neurons of the somatosensory cortex of rats at the end of the first postnatal week, a period of GABA-dependent cortical maturation. IFN-γ acutely increased the frequency and amplitude of spontaneous/ miniature inhibitory postsynaptic currents (s/mIPSC) and this could not be reversed within 30 minutes. Neither the increase in amplitude nor frequency of IPSCs was due to upregulated interneuron excitability as revealed by current clamp recordings of layer 5 interneurons labelled with VGAT-Venus in transgenic rats. As we previously reported in more mature animals, IPSC amplitude increase upon IFN-γ activity was dependent on postsynaptic protein kinase C (PKC), indicating a similar activating mechanism. Unlike augmented IPSC amplitude, however, we did not consistently observe increased IPSC frequency in our previous studies on more mature animals. Focusing on increased IPSC frequency, we have now identified a different activating mechanism – one that is independent of postsynaptic PKC but is dependent on inducible nitric oxide synthase (iNOS) and soluble guanylate cyclase (sGC). In addition, IFN-γ shifted short-term synaptic plasticity towards facilitation as revealed by a paired pulse paradigm. The latter change of presynaptic function was not reproduced by application of a nitric oxide donor. Functionally, IFN-γ -mediated alterations in GABAergic transmission overall constrained early neocortical activity in a partly nitric oxide dependent manner as revealed by multielectrode array field recordings in brain slices analyzed with a spike-sorting algorithm. In summary, with IFN-γ induced, NO-dependent augmentation of spontaneous GABA release we have here identified a mechanism by which inflammation in the central nervous system plausibly modulates neuronal development.